Sleep deprivation reduces the baroreflex sensitivity through elevated angiotensin (Ang) II subtype 1 receptor expression in the nucleus tractus solitarii - Liu, Ling-feng; Wang, Yu-wan; Sun, Jia-cen; Wang, Yang-kai; Tan, Xing; Wang, Wei-zhong (Frontiers in Neuroscience, 2024)
Sleep insufficiency has been linked to an increased risk of high blood pressure and cardiovascular diseases. Emerging studies have demonstrated that impaired baroreflex sensitivity (BRS) is involved in the adverse cardiovascular effects caused by sleep deprivation, however, the underlying mechanisms remain unknown. Therefore, the present study aims to clarify the role of abnormal renin-angiotensin system in the nucleus tractus solitarii (NTS) in impaired BRS induced by sleep deprivation. Rats were randomly divided into two groups: normal sleep (Ctrl) and chronic sleep deprivation (CSD) group. Rats were sleep deprived by an automated sleep deprivation system. The blood pressure, heart rate, BRS, the number of c-Fos positive cells and the expression of angiotensin (Ang) II subtype 1 receptors (AT1R) in the NTS of rats were assessed. Compared to Ctrl group, CSD group exhibited a higher blood pressure, heart rate, and reduced BRS. Moreover, the number of c-Fos positive cells and local field potential in the NTS in CSD group were increased compared with the Ctrl group. It was shown that the expression of the AT1R and the content of Ang II and the ratio of Ang II to Ang-(1-7) were increased in the NTS of rats in CSD group compared to Ctrl group. In addition, microinjection of losartan into the NTS significantly improved the impaired BRS caused by sleep deprivation. In conclusion, these data suggest that the elevated AT1R expression in the NTS mediates the reduced BRS induced by chronic sleep deprivation.